Ausgewählte Aspekte zur weiteren Entwicklung und Vertiefung des Problemverständnisses der Fremdsprachenpsychologie - MATZ, Klaus-Dieter (Wydawcnictwo Naukowe UAM, 1988)
The present paper critically evaluates the actual state of affairs of increasingly using psychological findings in the research of foreign language acquisition. After dealing with foreign language psychology as an emerging discipline of psychology as a whole, interdisciplinary as well as intradisciplinary fields of research will be introduced. Then dichotomous points of view inherent in theories of foreign language acquisition will be critically discussed. The author tries to present a cognitive-psychological approach to the formation of theories. On the basis of this approach computerized analyses will bo possible to work out training programmes for economizing procosses of foreign language acquisition.